2019
DOI: 10.3390/h8040166
|View full text |Cite
|
Sign up to set email alerts
|

Afropolitan Sexual and Gender Identities in Colonial Senegal

Abstract: Drawing from Achille Mbembe’s theorization of Afropolitanism as an opportunity for modern Africans “to experience several worlds” and develop flux, hybrid, and constantly mobile identities (“Afropolitanism” 29), this essay attempts to make an intervention into the ways in which this phenomenon appeared in colonial Senegalese culture. A neglected site of Afropolitanism was the colonial metropolis of Dakar which reflected subversive homosexual or transgender identities during the 1940s and 50s. Focusing on key w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This study further identified that time spent “living as a woman” was variable among participants identifying as transsexual or transgender, and authors acknowledged that varying concepts of the transfeminine identity may have led to misclassification. As explained by M’Baye, “studying transgenderism and homosexuality in African contexts is challenging” due to reliance on concepts that are primarily Western-derived [ 43 ]. Generating contextually centered knowledge on gender-related identities and experiences could lead to measures that better represent the health and well-being of trans- and gender non-conforming communities, and lead to development of interventions that better serve their needs.…”
Section: Discussionmentioning
confidence: 99%
“…This study further identified that time spent “living as a woman” was variable among participants identifying as transsexual or transgender, and authors acknowledged that varying concepts of the transfeminine identity may have led to misclassification. As explained by M’Baye, “studying transgenderism and homosexuality in African contexts is challenging” due to reliance on concepts that are primarily Western-derived [ 43 ]. Generating contextually centered knowledge on gender-related identities and experiences could lead to measures that better represent the health and well-being of trans- and gender non-conforming communities, and lead to development of interventions that better serve their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that the intentional politicization of homophobia under religious pressure has served as a reassertion of national integrity in the face of Western domination and as a tool of electoral support ( Angotti et al. , 2019 ; Bertolt and Masse 2019 ; M’Baye and Muhonja 2019 ). The media has also been a great contributor in depicting same-sex relationships as a decadent menace to society ( Mbaye, 2021 ).…”
Section: Introductionmentioning
confidence: 99%